Iatrogenic Cushing’s syndrome with inhaled steroid plus antidepressant drugs - Celik, Ozlem (BioMed Central, 2012)
Current guidelines recommend the use of inhaled corticosteroids (ICS) for suppression of airway inflammation in patients with asthma. Although it is well known that ICS cause dose-related adrenocortical suppression, it is less known that they can lead to iatrogenic Cushing’s syndrome (CS). Fluticasone propionate (FP) is an ICS more potent than beclomethasone and budesonide. FP is metabolized as mediated by cytochrome P450 3A4 in the liver and the gut. Systemic bioactivity of FP can increase with the use of drugs that affect the cytochrome P450. Herein, we report the rapid development of iatrogenic CS in a patient receiving paroxetine and mirtazepine for 12 weeks in addition to inhaled FP.